Strategi Komunikasi Dakwah Interpersonal: Analisis Dokumentasi Dakwah Gus Muhammad Iqdam Kholid di Youtube - Obianto, Agung; Yasir Nabhan, Mohamad (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
Interpersonal communication is one of the key elements in effective communications. The ability to communicate personally and in depth with the Jamaah can be a very powerful tool in conveying religious messages and building a close relationship with the Mad’u. The aim of this study is to find out how strategies of communications of devotion use interpersonal communication approaches. This research uses a descriptive qualitative approach with critical discourse analysis techniques. The subject of this research is the Gus Muhammad Iqdam Kholid, and its object is on Gus Mohammad Iqdan KHolid's document on the youtube platform. The data collection techniques used in this research are observation and documentation. As for the data analysis method used, the critical discourse analysis technique. Based on the results of this study, it is shown that the strategy of communication using the interpersonal communication approach of Gus Muhammad Iqdam Kholid exists two types, namely diadema and triadema. The mechanisms used are: 1. determining the theme or object of the conversation, 2. exchanging views and thoughts, 3. finding a better solution.